2005
DOI: 10.1523/jneurosci.4456-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Microglial Metabotropic Glutamate Receptor mGlu2 Triggers Tumor Necrosis Factor α-Induced Neurotoxicity in Concert with Microglial-Derived Fas Ligand

Abstract: Activated microglia may be detrimental to neuronal survival in a number of neurodegenerative diseases. Thus, strategies that reduce microglial neurotoxicity may have therapeutic benefit. Stimulation of group II metabotropic glutamate (mGlu) receptors on rat primary microglia with the specific group II agonist 2S,2ЈR,3ЈR-2-(2Ј,3Ј-dicarboxy-cyclopropyl)glycine for 24 h induced microglial activation and resulted in a neurotoxic microglial phenotype. These effects were attributable to preferential mGlu2 stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
221
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(237 citation statements)
references
References 66 publications
13
221
0
Order By: Relevance
“…MGluR2/3/5 is also expressed on microglia with varying modulatory effects. Glutamate binding to microglial mGluR2 promotes neurotoxicity via further release of inflammatory cytokines, glutamate, and nitric oxide (NO), whereas mGluR5 is neuroprotective through the opposing effects on same systems (Piers et al, 2011;Taylor et al, 2005). Considerable recent data implicate TNF in increasing microglial glutamate release.…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 99%
“…MGluR2/3/5 is also expressed on microglia with varying modulatory effects. Glutamate binding to microglial mGluR2 promotes neurotoxicity via further release of inflammatory cytokines, glutamate, and nitric oxide (NO), whereas mGluR5 is neuroprotective through the opposing effects on same systems (Piers et al, 2011;Taylor et al, 2005). Considerable recent data implicate TNF in increasing microglial glutamate release.…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 99%
“…TNFa, TNFb, FasL, TRAIL, and TWEAK). [85][86][87][88][89][90] The interaction of these ligands with their receptors, including TNF receptor 1, FasR, death receptor 4, death receptor 5, and TWEAKR, expressed by oligodendrocyte progenitor cells and neurons, can trigger apoptotic cell death. Death receptor activation triggers an extrinsic pathway of caspase-dependent cell death, or produces truncated Bid, leading to enhancement of Bax-dependent mitochondrial pore formation and cell death.…”
Section: Death Receptorsmentioning
confidence: 99%
“…At the same time, gp120 or CXCL12 binds microglial CXCR4 to stimulate the production of TNF-α. Interestingly, Taylor DL et al (2005) demonstrated that induction of microglial TNF-α is dependent on the stimulation of mGlu2, which is highly correlated with the microglial neurotoxic phenotype. Further, they found that TNF-α can induce neuronal apoptosis by directly binding to its receptor TNFR1 on the surface of neurons.…”
Section: Hiv-associated Encephalopathymentioning
confidence: 99%